The Market for Seamen in the Age of Sail. - Fischer, Lewis R. (Oxford : Liverpool University Press, 2017)
This volume collects eight essays that all attempt to answer two key concerns: did markets for seafarers exist in the age of sail; and, if so, were these markets efficient?
Cover; Title Page; Copyright Page; Contents; About the Editor; Contributors; Introduction; Maritime Labour in Early Modern Spain; Recruitment and Promotion: The Merchant Fleet of Salem, Massachusetts, 1670-1765; Mariners and Markets in the Age of Sail: The Case of the Netherlands""; Pirates and Markets; 'Advance Notes' and the Recruitment of Maritime Labour in Britain in the Nineteenth Century; Finnish and International Maritime Labour in the Age of Sail: Was There a Market?; The Efficiency of Maritime Labour Markets in the Age of Sail: The Post-1850 Norwegian Experience.
Print version record.
The Danish Maritime Labour Market, 1880-1900""
JSTOR
Keywords: Merchant mariners -- Supply and demand -- History; Merchant marine -- History; Marins (Marine marchande) -- Offre et demande -- Histoire; Marine marchande -- Histoire; Merchant marine; Merchant mariners -- Supply and demand; History